Histopathological Aspects of Gastritis in Children - Gabriela Păduraru; Marin Burlea; Doina Mihăilă; Smaranda Diaconescu; Claudia Olaru; Ancuța Ignat; Valeriu V. Lupu (Romanian Society of Oral Rehabilitation, 2012)
Introduction Gastritis are particularly important in paediatric pathology in Romania, considering the large number of hospitalized cases in recent years and also the trend of increasing incidence of disease. Objectives The authors have proposed to investigate a homogeneous group of patients diagnosed with different types of gastritis, in order to identify those bacteriological, endoscopic and histopathological features that can change the vision about optimal therapeutic attitude, prognosis and disease progression. Methods We studied a group of 96 patients who were hospitalized in Vth Paediatrics Clinic, Children's Emergency Hospital "Sf. Maria", Iasi, between January 2008 and December 2010 who have been diagnosed with various forms of gastritis. The final diagnosis was confirmed endoscopically, bacteriologically and histopathologically. Results Histopathological examination revealed the presence of H. pylori and also microscopic lesions that were assessed according to Sydney System. The associated microscopic lesions were exclusively of chronic gastritis. Mild form of disease was much rarer for H. pylori infection (5.26%) compared with H. pylori negative group (54.34%).The presence of lymphoid follicles was more frequently objectified in H. pylori-positive group (28.94%) compared with H. pylori-negative group (8.69%). In the H. pylori-positive group, the moderately-active form prevailed (31.57%), followed by follicular active form (28.94%) and massive active form (13.15%), while in the H. pylori-negative group most frequently was mild chronic gastritis (54.34%). Conclusions Histopathological examination presents a high relevance in assessing microscopic gastric mucosal lesions and also their evolution after treatment.